2013
DOI: 10.7314/apjcp.2013.14.5.2743
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Mutation Analysis of PIK3CA, p14ARF, p16INK4a and p21Waf1/Cip1Genes is Suggestive of a Non- Neoplastic Nature of Phenytoin Induced Gingival Overgrowth

Abstract: Background: Dilantin sodium (phenytoin) is an antiepileptic drug, which is routinely used to control generalized tonic clonic seizure and partial seizure episodes. A few case reports of oral squamous cell carcinomas arising from regions of phenytoin induced gingival overgrowth (GO), and overexpression of mitogenic factors and p53 have presented this condition as a pathology with potential to transform into malignancy. We recently investigated the genetic status of p53 and H-ras, which are known to be frequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…The PIK3CA hotspot mutations H1047R and E545K were frequently described in many human cancers including brain, breast, colorectal, gastric, lung, ovarian, and oral cancer (Samuels et al , ; Murugan et al , ). Although the PIK3CA mutation has been analyzed in South Indian patients, it was only on phenytoin‐induced gingival overgrowth, but not in oral cancer samples, and this study found no mutation in the analyzed samples (Swamikannu et al , ). We did not find any PIK3CA gene (exons 9 and 20) hotspot mutations in the South Indian oral cancer although the frequency of the PIK3CA has been shown to be ~10% of OSCC in Asian and Caucasian population (Kozaki et al , ; Qiu et al , ; Murugan et al , ).…”
Section: Discussionmentioning
confidence: 69%
“…The PIK3CA hotspot mutations H1047R and E545K were frequently described in many human cancers including brain, breast, colorectal, gastric, lung, ovarian, and oral cancer (Samuels et al , ; Murugan et al , ). Although the PIK3CA mutation has been analyzed in South Indian patients, it was only on phenytoin‐induced gingival overgrowth, but not in oral cancer samples, and this study found no mutation in the analyzed samples (Swamikannu et al , ). We did not find any PIK3CA gene (exons 9 and 20) hotspot mutations in the South Indian oral cancer although the frequency of the PIK3CA has been shown to be ~10% of OSCC in Asian and Caucasian population (Kozaki et al , ; Qiu et al , ; Murugan et al , ).…”
Section: Discussionmentioning
confidence: 69%